Agricultural dust explosions in 1998 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 18 dust explosions reported in the U.S. in 1998 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Ralph Regan, Safety Director, USDA-FGIS. This compares to 16 in 1997 and a ten-year average of 13.5 explosions.
Keywords: Grain dust; Dust explosions